2017
DOI: 10.1038/srep40627
|View full text |Cite
|
Sign up to set email alerts
|

Soluble urokinase receptor (suPAR) predicts microalbuminuria in patients at risk for type 2 diabetes mellitus

Abstract: Early identification of patients at risk of developing diabetic nephropathy is essential. Elevated serum concentrations of soluble urokinase receptor (suPAR) associate with diabetes mellitus and predict onset and loss of renal function in chronic kidney disease. We hypothesize, that suPAR may be an early risk indicator for diabetic nephropathy, preceding microalbuminuria. The relationship of baseline suPAR and incident microalbuminuria was assessed in a prospective long-term cohort of subjects at increased ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 29 publications
2
40
0
Order By: Relevance
“…The majority of the patient samples examined here also caused a substantial loss of podocin in cultured podocytes, consistent with previous reports [44,46]. Similar effects on TRPC6 and podocin were evoked by suPAR, a circulating factor that has been suggested to drive primary and recurrent FSGS [5,57] and which markedly increases risk for future chronic kidney disease [1012]. However, not all of the recurrent FSGS plasma samples showed this pattern.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The majority of the patient samples examined here also caused a substantial loss of podocin in cultured podocytes, consistent with previous reports [44,46]. Similar effects on TRPC6 and podocin were evoked by suPAR, a circulating factor that has been suggested to drive primary and recurrent FSGS [5,57] and which markedly increases risk for future chronic kidney disease [1012]. However, not all of the recurrent FSGS plasma samples showed this pattern.…”
Section: Discussionsupporting
confidence: 90%
“…Beyond the context of FSGS, large longitudinal studies have found that elevated blood suPAR levels in people with normal baseline renal function are associated with future chronic kidney disease and declines in estimated glomerular filtration rate [10,11]. Moreover, there is evidence that elevated serum suPAR levels predict future microalbuminuria in patients at risk for or with newly manifested type 2 diabetes mellitus [12]. In mice there is evidence that the circulating suPAR that drives kidney disease is derived from immature myeloid cells in bone marrow, and that transplantation of myeloid cells secreting high levels of suPAR can induce kidney disease in recipient mice [13].…”
Section: Introductionmentioning
confidence: 99%
“…10,18,20,21 On the other hand, suPAR has recently been demonstrated to be a sensitive predictor of early kidney damage and progression to CKD in adults. 1113,22 In this study, we provide evidence that (1) suPAR level is associate d with CKD progression throughout the eGFR range from 15 to 80 mL/ min/1.73 m 2 , and (2) the strength ofthe association with suPAR exceeds that of eGFR alone in patients with mild to moderate CKD, ie, eGFR ranging from 40 to 80 mL/min/1.73 m 2 . The association between suPAR level and the rate of decline in kidney function was independent of the presence of significant proteinuria, the other well-established risk marker of CKD progression.…”
Section: Discussionmentioning
confidence: 63%
“…A large two-cohort prospective observational study demonstrated that elevated serum suPAR levels precede the decline of renal function (independently of baseline GFR) and associate with faster progression of CKD 27 . This finding of suPAR predicting future CKD development (in an independent fashion from baseline GFR) was validated by Guthoff et al 29 as well as Schultz et al 30 . The former study sought to define the positive predictive value of suPAR for albuminuria development in type 2 diabetic patients.…”
supporting
confidence: 56%